Thermal stable zinc-based hybrid halides with high external quantum efficiency as temperature detectors. Issue 36 (30th August 2022) - Zhang, Xusheng; Xiong, Yan; Liu, Kunjie; Wang, Na; Fan, Liubing; Li, Weiwei; Zhao, Xiaobin; Zhao, Jing; Liu, Quanlin
Abstract : (C9 H15 N3 )ZnCl4 with a very high external quantum efficiency and thermal quenching temperature was obtained. (C9 H15 N3 )ZnCl4 : Mn 2+ (5%) exhibited photoluminescence response, which may be applied as low temperature detectors. Abstract : Low-dimensional organic–inorganic metal halides with broad light emission have drawn widespread attention, however, the low thermal stability has been a major obstacle to their commercialization. Herein, zero-dimensional (C9 H15 N3 )ZnCl4 with space group P 21 was synthesized for the first time. (C9 H15 N3 )ZnCl4 emits blue fluorescence at room temperature with external quantum efficiency as high as 42.5%, which are among the highest reported for Zn-based OIMHs, and it is comparable with the commercialized phosphors. Notably, the luminous integral intensity of (C9 H15 N3 )ZnCl4 at 470 K remains more than 50% of that at room temperature. Mn 2+ doping of (C9 H15 N3 )ZnCl4 was conducted to improve the photoluminescence. With increasing Mn 2+ concentration, the title compounds underwent fluorescence conversion from blue to green. The external quantum efficiencies of (C9 H15 N3 )ZnCl4 : 5%Mn 2+ and (C9 H15 N3 )ZnCl4 : 50%Mn 2+ were 43.7% and 42.9%, respectively. More importantly, (C9 H15 N3 )ZnCl4 : 5%Mn 2+ exhibited different luminous colors at different temperatures. As the temperature decreased from 290 to 110 K, the luminous color changed from green to light blue. Finally, a composite film was prepared to demonstrate the temperature response of this material, and the absolute sensitivity reaches 0.57%/K. These findings fill in the gaps for low-temperature indication and expand the application scenarios of OIMHs.